The Influence of Work Environment and Organizational Culture on Employee Deviant Behavior with Job Stress as an Intervening Variable: A Study at PD BPR Bank Wonosobo - Akmal, Nabil Aushaf; Dihan, Fereshti Nurdiana (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study examines the influence of work environment and organizational culture on employee deviant behavior, with job stress as an intervening variable, at PD BPR Bank Wonosobo. Human resources play a crucial role in sustaining service quality and corporate reputation, where a supportive environment, strong culture, and effective stress management are essential for optimal performance. A quantitative approach was employed using a structured questionnaire distributed to 109 employees through a census technique. Data analysis included descriptive statistics, measurement model assessment, structural model testing, and mediation analysis. The findings indicate that work environment and organizational culture both have a negative and significant effect on job stress, and similarly exert a negative and significant effect on deviant behavior. These results suggest that organizations should foster a supportive work environment, strengthen positive cultural values, and manage employee stress effectively to minimize deviant behavior and enhance productivity.